Model Pembelajaran yang Menyenangkan Berbasis Gaya Belajar pada Peserta Didik - Sandy Diana Mardlatillah; Nurus Sa’adah (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2022)
Teachers as one of the successes of curriculum implementation must prepare themselves, understand various concepts and learning models. A fun, creative and interesting learning model is recommended to be applied during the learning process. Due to the diversity of students' abilities in absorbing material, not a few students experience learning difficulties due to conventional teaching. In addition, there are characteristics in learning related to absorbing, processing and conveying learning information, namely learning styles. Learning style is a very important learning modality. The purpose of this research is how to apply the concepts of fun learning based on learning styles. The method used in this research is qualitative. The method used in this research, so that most of the literature used to explore data sources comes from library materials and other relevant references such as books and journals. The results of this study are learning models that are applied to fun learning based n learning styles including the brain based learning model, role playing model, make a match, black knight, paikem, poe (predict-observe-explaint), game and humor.